Uji Model Fisik Stabilitas Bangunan Sekat Kanal Bentang 5 Meter dengan Material Konstruksi Terbuat dari Kayu - Ervina; Haiki Mart Yupi; Dwi Anung Nindito (Program Studi Teknik Sipil Fakultas Teknik Universitas Palangka Raya, 2023)
Forest and land fires are one of the most concerning incidents. One effort to overcome this problem is to reblocktheexistingcanalsusingablock/damsystem.Itishopedthatthewaterlevelinthecanalsonpeatlands canbeincreasedsoastoreducetheriskoffiresduringthedryseason.However,theinformationavailable regarding canal blocking is still very limited. This study aims to determine the stability of canal blockingstructures against shear, stability of overthrowning force and seepage by conducting physical model tests.This research method uses the observation method. The research location was carried out in the city ofPalangka Raya, starting from March 19 2022 to May 24 2022. This research was carried out by directlyobserving the changes that occurred in the physical model of canal blocking. The results showed that thestability against sliding and stability of overthrowning force was stated to be safe. Seepage continues tooccur in the downstream part of the canal blocking, whose value increases with the increase in the waterlevel in the upstream section as time increases.